# Algebra

posted by .

3x^2 + 10x - 5 = 0.

• Algebra -

[-10 +/- sqrt(100 +60) ] / 6

[-10 +/- 4 sqrt(10) ] / 6

-5/3 +/- (2/3) sqrt 10

## Similar Questions

1. ### Math

Find the equation of the tangent line 5x^2+y^2=14 at (1,3). P.S: It's calculus. So far I know this much 10x+2y(dy/dx)=o -10x -10x ___________________ 2y(dy/dx)= -10x (dy/dx)= -10x/2y= -5x/y m= -5(1)/3= -5/3 y=mx+b 3= -5/3(1)+b then …
2. ### AP Chemistry

i'm having trouble balancing the redox reaction for the iodine clock lab. The redox reaction inovlves a hydrogen sulfite ion and iodate ion in an acidified solution. i have the final balanced equation, 5 HSO3 + 2 IO3 ---> I2 + 5SO4 …
3. ### Intermediate Algebra

Determine whether the point (1, 8) is a solution of the system 2x + 6y = 50 10x + 0y = 10 by substituting the point into each equation. So far I have: 2x=6y=50 y=50-2x 10x+10y=10 10x+0(50-2x)=10 10x+0=10 x=10 y=50-2x y=50-2(1) y=50-2 …
4. ### Math 141

I am having trouble with this problem. perform the indicated operations and simpily the result as much as possible a) (3x - 2) (x^2 + 2x - 4 ) the answer i got so far is 3x^3 + 4x^2 -16x + 8. Am i done or i have to conitnue to simplify?
5. ### Algebra

I'm having trouble with this literal equation. r^2/r^2+a^2=w/x solve for w. Thanks so much for the help
6. ### math

When the problem says "Angel transformed the following equation from 6x+4-×=2 (×+1) to 10=2 (×+1). He then stated that the solution to the equation is ×=4. Is he correct?
7. ### math

When the problem says "Angel transformed the following equation from 6x+4-×=2 (×+1) to 10=2 (×+1). He then stated that the solution to the equation is ×=4. Is he correct?
8. ### Geometry

If /BC bisects ÚABD, and ÚABC = 5x + 11, ÚCBD = 10x − 4, then find x. 5 3 1 2 I am having trouble with this one, please help.
9. ### algebra

Please help, I am really having trouble understanding this problem. what are the foci of the hyperbola given by the equation 16y^2-9x^2=144
10. ### Math - Calc 2/Algebra

I'm trying to find the partial fraction decomposition of: 10x^2+2x-2/x^2(x+1) I already found B=-2 and C=6 Plugging in the numbers, I get: 10x^2+2x-2=Ax(x+1)+(-2)(x+1)+(6)x^2 How do I solve this for A?

More Similar Questions